Let's find solutions together at Johnmiedema.ca, the best Q&A platform. Are you looking for answers? We have solutions.

## Sagot :

x - y = 29

x = 17 - y

x - y = 29

x = 17 - y

17 - y - y = 29

x = 17 - y

17 - 2y = 29

x = 17 - y

- 2y = 29 - 17

x = 17 - y

-2y = 12

x = 17 - y

y = -6

x = 17 - (-6)

y = -6

x = 17 + 6

y = -6

x = 23

y = -6

**Answer:**

x + y = 17

x - y = 29

x = 17 - y

x - y = 29

x = 17 - y

17 - y - y = 29

x = 17 - y

17 - 2y = 29

x = 17 - y

- 2y = 29 - 17

x = 17 - y

-2y = 12

x = 17 - y

y = -6

x = 17 - (-6)

y = -6

x = 17 + 6

y = -6

x = 23

y = -6

Read more on Brainly.com - https://brainly.com/question/14264#readmore

**Step-by-step explanation:**